2019
DOI: 10.1101/815175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting behaviour of malaria vectors in a highland and a lowland site of western Kenya: Implication on malaria vector control measures

Abstract: 33Background: Understanding the interactions between increased insecticide resistance in field 34 malaria vector populations and the subsequent resting behaviour patterns is important for planning 35 adequate vector control measures in a specific context and sustaining the current vector 36 interventions. The aim of this study was to investigate the resting behavior, host preference and 37 infection with Plasmodium falciparum sporozoites by malaria vectors in different ecological 38 settings of western K… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…gambaie were responsible for malaria transmission both indoors and outdoors in the lowland and highland sites respectively, with majority of malaria infections occurring outdoors. The ndings are in agreement with previous studies that observed the two vectors to be the main drivers of malaria transmission in the region [25,26,29], however contrary to the present study, the early studies reported high infection rates indoors. It's worth mentioning that high bed net ownership and usage of > 90% was con rmed in all three sites.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…gambaie were responsible for malaria transmission both indoors and outdoors in the lowland and highland sites respectively, with majority of malaria infections occurring outdoors. The ndings are in agreement with previous studies that observed the two vectors to be the main drivers of malaria transmission in the region [25,26,29], however contrary to the present study, the early studies reported high infection rates indoors. It's worth mentioning that high bed net ownership and usage of > 90% was con rmed in all three sites.…”
Section: Discussionsupporting
confidence: 92%
“…In the highlands (Kimaeti), only An. gambiae was collected, with previous studies con rming the species to be dominant in the region [29,44]. This vector showed no change in biting activity as the results indicate that the species preferred feeding indoors with a pronounced activity late at night between 0100-0200 h. Historical studies have reported man to be the principal host for this species unlike its sibling species An.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The malaria vector Anopheles arabiensis has been reported with increasing levels of kdr mutations [19]. There are no reports of kdr mutation at the locus 1014 in Anopheles funestus, also an important vector in Western Kenya and many parts of Africa despite having several reports of metabolic resistance [20][21][22]. The increasing levels of insecticide resistance in malaria mosquitoes have been associated with continuous exposure to insecticides in Long Lasting Insecticide Nets( LLINs) [23,24] and agro-chemicals such as pesticides due to the creation of selection pressures [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The malaria vector Anopheles arabiensis has been reported with increasing levels of kdr mutations [19]. There are no reports of kdr mutation at the locus 1014 in Anopheles funestus, also an important vector in western Kenya and many parts of Africa despite having several reports of metabolic resistance [20][21][22]. The increasing levels of insecticide resistance in malaria mosquitoes is believed to be mainly caused by scaling up of insecticidal treated nets (ITNs) [23,24] and indiscriminate use of agro-chemicals for controlling crop pests in agriculture [25][26][27].…”
Section: Introductionmentioning
confidence: 99%